The effect of bidalak on netra karshnya (dark circles): Array - Deshmukh, Amol Ashokrao; Unavekar, Anagha; Ingale, P. D. (Ayurline: International Journal of Research in Indian Medicine, 2019)
Patients observed in opd of Arogyashala Rugnalay Nashik with netra karshnya were selected for the present study, and dashang lep bidalak was done on netra vartma mandal. It is observed that there is prakop of vaat dosh by laghu, ruksha, khar, sheet, sukshma gun which lead to netra karshnya. Dashnag lep applied on the netra vartma affected by netra karshnya. The effect of dashang lep bidalak was observed and noted.